Analyzing the influence of principals' instructional leadership, teachers' attitudes toward change, and schools' collaborative learning cultures on educational reform in learning - Ying Hu; Ibrahim Duyar (Future in Educational Research)
Abstract The purpose of this study was to examine the influence of principals' instructional leadership, teachers' attitudes toward change, teachers' attitudes toward school museums' instructional mission, and schools' collaborative learning culture on students' level of key competencies (e.g., cognitive, creative, and cooperative competencies). A special emphasis was given to the examination of whether the school contexts in the form of school museums have any significant influence on student learning. A random sample of 22 public schools with museums was selected from four cities in China (Shanghai, Shaoxing, Hangzhou, and Foshan). A total of 111 school teachers and 1171 students were included as participants. Multilevel confirmatory factor analysis and structural equation modeling were employed to analyze multisource survey data. Findings revealed that principals' instructional leadership positively influenced students' key competencies, which was mediated by teachers' attitudes toward school museums' instructional mission and schools' collaborative learning culture. Similarly, teachers' attitudes toward change positively predicted students' key competencies. The findings of the study suggest that school museums can be instrumental in improving student learning and, thus, may contribute to large‐scale learning policy changes that incorporate cognitive learning with noncognitive, social, and emotional aspects of learning.